2021
DOI: 10.1186/s12879-021-06783-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and risk factors analysis of bronchitis obliterans due to refractory Mycoplasma pneumoniae pneumonia in children: a nomogram prediction model

Abstract: Background Early prediction of bronchitis obliterans (BO) is of great significance to the improvement of the long-term prognosis of children caused by refractory Mycoplasma pneumoniae pneumonia (RMPP). This study aimed to establish a nomogram model to predict the risk of BO in children due to RMPP. Methods A retrospective observation was conducted to study the clinical data of children with RMPP (1–14 years old) during acute infection. According to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…Our study confirmed that consolidation size corrected for BSA remained an independent risk factor for RMPP and entered the prediction model. Several studies confirmed 7,12,26 that unilateral pulmonary solidity or atelectasis was the most critical risk factor for developing RMPP, which was consistent with our findings. Musolino et al 35 showed that 63.6% of patients with complicated pneumonia had a lung consolidation size ≥5 cm in LUS.…”
Section: Dovepresssupporting
confidence: 92%
See 2 more Smart Citations
“…Our study confirmed that consolidation size corrected for BSA remained an independent risk factor for RMPP and entered the prediction model. Several studies confirmed 7,12,26 that unilateral pulmonary solidity or atelectasis was the most critical risk factor for developing RMPP, which was consistent with our findings. Musolino et al 35 showed that 63.6% of patients with complicated pneumonia had a lung consolidation size ≥5 cm in LUS.…”
Section: Dovepresssupporting
confidence: 92%
“…Among predictive models, including laboratory indicators, recent studies have found that the levels of LDH and CRP 9 in the blood are the best predictors of RMPP. Some studies have also found inflammatory indicators in the blood, such as DD, 10 SF, IL-18, 11 ALB, 12 the neutrophil-to-lymphocyte ratio (NLR) and the mean platelet volume-to-lymphocyte ratio (MPVLR), 13 are suitable for predicting RMPP. Increased IL-17A in bronchoalveolar lavage fluid is an independent risk factor for RMPP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al retrospectively analyzed the clinical baseline characteristics of 64 children in China and further created a recurrence risk model of children Neurophyllitis optica spectrum disorders using a nomogram [ 17 ]. Cheng et al analyzed the clinical characteristics and risk factors for the development of PIBO in children (0–14 years old) with refractory Mycoplasma pneumoniae pneumonia (MPP) and constructed a nomogram to predict the risk ratio for the development of PIBO [ 18 ]. Similarly, the current study analyzed the risk factors for the development of PIBO in 66 children (0–36 months) with ADVP after IMV retrospectively and constructed a nomogram.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, our study further analyzed the occurrence of PIBO in children with ADVP after IMV and constructed a nomogram to predict the risk ratio for PIBO. Cheng et al constructed a nomogram model for the occurrence of PIBO by analyzing the data of 141 children with MPP (aged 1–14 years) [ 18 ]. Unlike the study by Cheng et al [ 18 ], our study was conducted on children with ADVP aged 0–3 years and not on children with MPP aged 1–14 years.…”
Section: Discussionmentioning
confidence: 99%